Uptake of Bowel Scope (Flexible Sigmoidoscopy) Screening in the English National Programme: the first 14 months. (June 2016) - McGregor, Lesley M; Bonello, Bernardette; Kerrison, Robert S; Nickerson, Claire; Baio, Gianluca; Berkman, Lindy; Rees, Colin J; Atkin, Wendy; Wardle, Jane; von Wagner, Christian
Objective: To examine uptake in the first six pilot centres of the English Bowel Scope Screening (BSS) programme, which began in early 2013 and invites adults aged 55 for a one off Flexible Sigmoidoscopy. Methods: Between March 2013 and May 2014 the six pilot centres sent 21, 187 invitations. Using multivariate logistic regression analysis, we examined variation in uptake by gender, socioeconomic deprivation (using the Index of Multiple Deprivation), area-based ethnic diversity (proportion of non-white residents), screening centre, and appointment time (routine: daytime vs out-of-hours: evening/weekend). Results: Uptake was 43.1%. Men were more likely to attend than women (45% vs 42%; OR 1.136, 95% CI 1.076, 1.199, p < 0.001). Combining data across centres, there was a socioeconomic gradient in uptake, ranging from 33% in the most deprived to 53% in the least deprived quintile. Areas with the highest level of ethnic diversity also had lower uptake (39%) than other areas (41–47%) (all p < 0.02), but there was no gradient. Individuals offered a routine appointment were less likely to attend than those offered an out-of-hours appointment (42% vs. 44%; OR 0.931, 95% CI 0.882, 0.983, p = 0.01). Multivariate analyses confirmed independent effects of deprivation, gender, and centre, but not of ethnic diversity or appointment time. Conclusion: Early indications of uptake are encouraging. Future efforts should focus on increasing public awareness of the programme and reducing socioeconomic inequalities.